KARAKTERISTIK WANITA USIA SUBUR YANG MELAKUKAN INSPEKSI VISUAL ASAM ASETAT DI KELURAHAN RENON - Nurtini, Ni Made; Dewi, Komang Purnama; Puspita Dewi, Ni Wayan Erviana (Jurnal Riset Kesehatan Nasional, 2017)
Introduction: Prevention of cervical cancer can be done by screening and vaccination programs. The purpose of this study to identify the specific characteristics of women of reproductive age (WUS) that do early detection methods Visual Inspection Acetic Acid (VIA) by age group, education level, occupation, level of knowledge, of marriageable age, economic level, parity, and contraceptive use on time of inspection and examination results IVA IVA. Methodology: The methodology used descriptive cross sectional with the entire population of WUS inspecting IVA in the village of Renon in May 2016. The sample in this study is total sampling. Results: The age test in the village of Renon IVA is aged 25-56 years. Some 45.5% of respondents educated past high school. Most respondents had good knowledge. The age of first married at age> 20 years is 77.8%. Monthly family income of 27 respondents 51.9%. From the results of implementation effectiveness of the research, 37.9% of respondents are housewives and 27.3% are self-employed. WUS more use of the IUD, with duration of use of no more than 5 years. The majority of respondents had 1 to 2 children. Discussion: This study shows that are coming are of reproductive age with the most educated high school, most of the knowledge of good, most aged married at the age of> 20 years. Income and employment do not affect the visit IVA. WUS who use non-hormonal birth control are more to come. The more often a woman gave birth to the higher risk for cervical cancer. The results have been positive IVA referral to services at the facility higher for Cryo.Keywords: Visual Inspection acid acetate, Women of fertile age